The Way Forward Lean Leadership and Systems Thinking for Large and Small Businesses. - Garneau, Wallace (Milton : Productivity Press, 2021)
This bookhelps business leaders see how employees, companies, and missions all interact with each other, as well as with society at large, in systems and subsystems at various levels. It helps leaders learn how to connect the dots, becoming customer-centric in everything they do and then spreading the same goals down to their supply chains. The book discusses what is, and what is not, leadership, covering such topics as statistics-based management, process-improvement, and human resources. The author accomplishes this through a blend of Lean culture and managerial theory, as well as his military experience. In addition, the author contrasts many opposing subjects, such as efficiencies of scale versus efficiencies of build, automation versus process improvement, process innovation versus product innovation, technical versus tactical proficiency, and pull versus push production. With most books focused on Lean initiatives, there is a tremendous amount of benefit involved in creating customer value while reducing waste, but this book takes a holistic approach, blending in modern managerial theory, team leadership skills, and economics. The result is a book that changes how the reader approaches business. Essentially, the purpose of this book is to blend modern management theories with the culture of Lean (and perhaps a sprinkling of economics) to show current business leaders how to create organizations that are as customer-oriented and highly efficient in delivering value as possible. If one thinks of each role in an organization as a spot on an assembly line, where everything each person does creates output someone else uses, the question becomes whether or not each person's activities maximize the effectiveness of others. Do we, as organizations, set ourselves up for success or for failure? Most companies, if they answer honestly, would say, "A little bit of both." This book is about helping those companies improve.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: Leadership; Lean manufacturing -- Management; Success in business; BUSINESS & ECONOMICS / Production & Operations Management; BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Workplace Culture